Hepatitis B vaccine knowledge and self-reported vaccination status among healthcare workers in a conflict region in northeastern Nigeria - Farouq Muhammad Dayyab; Garba Iliyasu; Bashir Garba Ahmad; Abdulaziz Tijjani Bako; Sepu Saraya Ngamariju; Abdulrazaq Garba Habib (SAGE Publishing, 2020)
Background Hepatitis B virus (HBV) infection is highly endemic in Nigeria. The primary objective of this study is to describe the knowledge, self-reported vaccination status, and intention of healthcare workers to receive hepatitis B vaccine at a tertiary referral center in conflict-ravaged northeastern Nigeria. Methods This was cross-sectional analytical study among medical practitioners, nurses, laboratory workers, health attendants, pharmacists, and radiographers working at Federal Medical Center Nguru, Yobe State. Written informed consent was obtained from all study participants. Data were obtained using questionnaires and entered into a Microsoft Excel spreadsheet, cleaned and analyzed using JMP Pro software. Results Of the 182 participants, we found that 151 (82.97%), 81 (44.51%), 85 (46.70%), and 33 (18.13%) had good knowledge of HBV, good knowledge of hepatitis B vaccine, were vaccinated against HBV by the least dose, and had a complete hepatitis B vaccination status, respectively. The lack of availability of the vaccine was the main reason for not receiving the vaccine among the unvaccinated 36/91 (39.56%), followed by not knowing where to access the vaccine 19/91 (20.88%). Conclusion The study highlights the need for strategies to ensure the availability of hepatitis B vaccine in conflict settings and need for vaccinology training given the suboptimal level of awareness and uptake of the hepatitis B vaccine among the healthcare workers.